Design and evaluation of a multilanguage instant messaging application - Ahmed, Ahmed Nabeel; Chit, Suwannit Chareen; Omar, Mohd. Hasbullah (2016)
Recent growth in mobile Internet has resulted in the emergence of instant messaging (IM) applications.These applications now allow users to communicate via text and voice messaging, as well as sending attachments to their intended recipients.While these applications now support multiple languages, they, only allow users to communicate using the same language.A communication barrier and breakdowns occur when users do not speak the same language.This paper describes the design of Multilingual Instant Messaging Application (MIMA), and measure the level of acceptance of the application.Respondents agree that MIMA is both useful and easy to use, and this application is an essential tool to bridge the communication gap between speakers of different languages